IMPLEMENTASI MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN MINAT DAN BAKAT MELALUI EKSTRAKURIKULER DI SMA DARUSSALAM BLOKAGUNG BANYUWANGI - Maharani, Lia Kholida Putri; Kurniawan, Nanang (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2022)
The importance of increasing interests and talents through extracurriculars for the 2021-2022 academic year, so that the interests and talents of students at Darussalam Blokagung High School can go according to what students have and not only focus on general science because students have many interests and talents which needs to be improved, thus it is necessary to have mature and good management so that extracurricular activities run effectively and efficiently. This type of qualitative descriptive research, namely by collecting data from interviews, documentation, and observation. The number of informants in this study was 3 people consisting of the Principal, Extra Coordinator, and Vice Chair (Student Affairs). And using data reduction analysis that directs, discards unnecessary, classifies, and organizes data so that final conclusions can be drawn. The results of this study are 1) Management of students at SMA Darussalam Blokagung Tergalsari Banyuwangi is the management of all activities related to students to achieve their goals and hopes in the future according to the conditions of different students. 2) Students at Darussalam Blokagung Tergalsari Banyuwangi High School have various abilities and desires, both in the realm of contract, 3) Implementation of student management at Darussalam Blokagung High School includes four stages namely planning, implementation, and evaluation.